Overall water splitting by Pt/g-C3N4 photocatalysts without using sacrificial agents. Issue 5 (3rd February 2016) - Zhang, Guigang; Lan, Zhi-An; Lin, Lihua; Lin, Sen; Wang, Xinchen
Abstract : Direct splitting of pure water into H2 and O2 in a stoichiometric molar ratio of 2 : 1 by conjugated polymers via a 4-electron pathway was established for the first time, as demonstrated here using a g-C3 N4 polymer and redox co-catalysts of Pt and Co species. Abstract : We report the direct splitting of pure water by light-excited graphitic carbon nitride (g-C3 N4 ) modified with Pt, PtO x, and CoO x as redox cocatalysts, while pure g-C3 N4 is virtually inactive for overall water splitting by photocatalysis. The novelty is in the selective creation of both H2 and O2 cocatalysts on surface active sites of g-C3 N4 via photodeposition triggering the splitting of water for the simultaneous evolution of H2 and O2 gases in a stoichiometric ratio of 2 : 1, irradiated with light, without using any sacrificial reagents. The photocatalyst was stable for 510 hours of reaction.